Investigation of atmosphere middle level changes center affecting on dry day of Zab catchment using PCA - nader parvin (تحقیقات کاربردی علوم جغرافیایی)
studying and identifying the middle levels change affecting the formation of a circular pattern creation is inevitable. In this study, the annual rainfall data for selected stations Zab River Basin during the period 2015-1986 were the standard time. After indexing and spatial-temporal threshold, 184 days without rainfall were selected in the wet period of three severe drought in the region. Level 500 HP height data located in the range of 0 to 80 degrees northern latitude and eastern longitude on dry days as a matrix S_Mode were used and these data using principal component analysis were processed using modern statistical methods. Based on the correlation matrix, the main focus of the 500 HP topography of the basin dry days were identified and analyzed. The results show that, in the happening time of dry days, twelve atmospheric middle levels of height change focus have been effective. In this regard, the following two centers having the highest anomalies (R≥0.7) are detected according to the high levels of the atmosphere: 1) the center of Eurasia-Africa, 2) the center of West Africa, respectively, 48% and 10% of the total area of the study. Such changes in middle atmospheric levels cause to strengthen and deepen the traffic axis and on the ridges. In the meantime, the change of first center has the highest impact on creation of stability and domination of dryness in days of Zab River Basin.